An Analysis of Violation of Cooperative Principle Maxim in The Rush Hour Movie 1 - Pahril, Afiq; Zaim, M. (Universitas Negeri Padang, 2024)
This study aims to find out the maxim that are classified as violating by the main characters in Rush Hour Movie 1 and to find out the maxim violation by the main characters influence to the characterization in the movie. This study uses a descriptive approach. Data and data sources are taken from the dialogues of the main characters which they are Lee and Carter in the Rush Hour Movie 1 movie. Data collection was carried out by analyzing using Grice's theory (1975). The results of the data obtained from this study are that there are 4 maxims that are violated in Rush Hour Movie 1 with a total of 27 maxim violations. Of the 4 maxims, there are 14 violations of the maxim of quality, 2 violations of the maxim of quantity, 6 violations of the maxim of relevance, and 5 violations of the maxim of manner. This study provides valuable insight into how the cooperative principle does not occur properly due to the violation of maxims in their communication, then, the characterizations main characters that are violated from the four maxims are Liar, Braggart, Narcissitic, Overstate, Not Relevant, Unresponsive, Ambiguity, and Insolent.